Selective dopamine D2 receptor deletion from Nkx6.2 expressing cells causes impaired cognitive, motivation and anxiety phenotypes in mice - Bechelli, Maria Lucila (2023)
Abnormal dopamine neurotransmission is a common trait of some psychiatric diseases, like schizophrenia or bipolar disorder. Excessive dopaminergic tone in subcortical brain regions is associated with psychotic episodes, while reduced prefrontal dopaminergic activity is associated with impaired cognitive performance and reduced motivation, among other symptoms. Inhibitory interneurons expressing the calcium binding protein parvalbumin are particularly affected in both schizophrenia and bipolar disorder, as they set a fine-tuned physiological inhibitory/excitatory balance. Parvalbumin and somatostatin interneuron subtypes, are born from the medial ganglionic eminence and require the sequential expression of specific transcription factors for their specification, such as Nkx6.2. Here, we aimed at characterizing in detail interneuron subtypes derived from Nkx6.2 expressing progenitors by the generation of an Nkx6.2 Cre transgenic mouse line. We show that Nkx6.2 specifies over a third part of the total population of cortical somatostatin interneurons, preferentially at early developmental time points, whereas at late developmental stages, Nkx6.2 expressing progenitors shift to parvalbumin interneuron specification. Dopamine D2 receptor deletion from Nkx6.2 expressing progenitors causes abnormal phenotypes restricted to cognitive, motivation and anxiety domains. Our results show that Nkx6.2 have the potential to specify both somatostatin and parvalbumin interneurons in an opposite timed program and that DRD2 expression is required in Nkx6.2 expressing progenitors to avoid impaired phenotypes commonly associated to the pathophysiology of psychiatric diseases.